Peningkatan Hasil Belajar IPS melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas IX SMPN 3 Wanasaba - Raehanun, Baiq Hijratul (Lembaga Yasin AlSys, 2022)
The learning approach with the STAD (Student Teams Achievement Divisions) cooperative learning model is a learning concept that helps teachers relate the material taught to students' real-world situations and encourages students to make connections between the knowledge they have and its application in their lives as members of the family and society. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of student work and experience activities, not transferring knowledge from teacher to student. A learning strategy is far more important than a result. The purpose of this classroom action research (CAR) is to find out how far the learning outcomes of Social Sciences (IPS) students have increased by applying the STAD (Student Teams Achievement Divisions) cooperative learning model. In class action research (PTK) this was carried out in 2 cycles, the results of the actions taken proved to be able to improve student learning outcomes by achieving ideal standards. From 74.2% in cycle I, it can increase in cycle II to 85.39%. The results of this action research indicate that the application of cooperative learning model type STAD (Student Teams Achievement Divisions) can improve student learning mastery in social studies subjects with mastery reaching 85.39%.